Sistem Pakar Diagnosa Penyakit Ikan Nila (Oreochomis Niloticus) Berbasis Web Menggunakan Metode Forward Chaining - Sriyadi Sriyadi; Nurhasanah Nurhasanah; Taufik Baidawi (Paradigma, 2018)
Fish is very beneficial for humans because it constains a wide variety of subtances needed by the human body. In the process of cultivation and seeding tilapia, fish farmers or farmers having some problems, one of the obstacle is disease in farmed tilapia.by using web based expert system using a forward chaining method tilapia fish farmers do not meet and consult with experts in fhisheries. This expert system is able to identify the disease tilapia and provide information on preventive and early treatment in order to minimize the time, effort, amd cost